κ- and μ-Opioids Reverse the Somatostatin Inhibition of Ca(2+) Currents in Ciliary and Dorsal Root Ganglion Neurons - Polo-Parada, Luis (J Neurosci, 1999)
Neuromodulators, including transmitters and peptides, modify neuronal excitability. In most neurons, multiple neuromodulator receptors are present on a single cell. Previous work has demonstrated either occlusive or additive effects when two neuromodulators that target the same ion channel are applied together. In this study, we characterize the modulation of Ca(2+) and K(+) channels in embryonic chick ciliary ganglion neurons by somatostatin (Som) and opioids, including the effects of these neuromodulators when applied in combination. We report a modulation of calcium current by κ- or μ-opioids that can prevent Som effects when applied before Som and can replace Som effects when applied after Som. We term these effects demodulation because they do not have the characteristics of simple occlusion but rather represent a dominant effect of opioid-mediated modulation of calcium channels over Som-mediated modulation. These opioid effects persist in the presence of kinase and phosphatase inhibitors, as well as after alteration of the intracellular Ca(2+) concentration. Furthermore, they are present in both whole-cell and perforated-patch recording configurations. These effects of opioids on Som-mediated modulation do not seem to be mediated by a general uncoupling of Som receptors from G-protein–coupled signaling systems because K(+)current modulation by Som can persist in the presence of opioids. Demodulation by opioids was also observed in dorsal root ganglion neurons on the modulation of calcium current by GABA and norepinephrine (NE). In both preparations, this demodulatory interaction occurred between voltage-independent (opioids) and voltage-dependent (Som, GABA, and NE) modulatory pathways.